2021
DOI: 10.1007/s00228-020-03066-w
|View full text |Cite
|
Sign up to set email alerts
|

Ivabradine use in pregnant women—treatment indications and pregnancy outcome: an evaluation of the German Embryotox database

Abstract: Purpose Ivabradine has been approved for the treatment of chronic heart failure and chronic stable angina pectoris in Europe. Based on adverse outcomes of reproductive animal studies and the lack of human data, ivabradine is considered contraindicated during pregnancy. The aim of this observational study is to analyse ivabradine use before and during pregnancy. Methods We evaluated all ivabradine-related requests to the German Embryotox Institute from 2007… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Ivabradine is given better tolerance and heart rate control in inappropriate sinus tachycardia than bisoprolol (Martino et al 2021). Ivabradine has been known as teratogenic in some animal studies, and future studies are required to refute other findings by Hoeltzenbein M et al, which have shown a low teratogen risk (Hoeltzenbein et al 2021). Trimetazidine has shown no significant reduction in blood pressure compared to nitrates, with the additional benefit of improved left ventricular systolic performance (Meiszterics et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Ivabradine is given better tolerance and heart rate control in inappropriate sinus tachycardia than bisoprolol (Martino et al 2021). Ivabradine has been known as teratogenic in some animal studies, and future studies are required to refute other findings by Hoeltzenbein M et al, which have shown a low teratogen risk (Hoeltzenbein et al 2021). Trimetazidine has shown no significant reduction in blood pressure compared to nitrates, with the additional benefit of improved left ventricular systolic performance (Meiszterics et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…20 Ivabradine is also frequently used in treating SVT. 21,22 However, its official use necessitates larger-scale clinical trials with more patients.…”
Section: Ivabradine Drug Mechanismmentioning
confidence: 99%
“…In the case of accidental ivabradine exposure or the absence of other treatment options, the study recommended fetal ultrasound for structural anomalies and growth restriction. 21 After oral administration, ivabradine absorption is nearly complete, with peak plasma levels reached in about 1 hour. Because of the first-pass effect in the gut and liver, it has approximately 40% bioavailability.…”
Section: Ivabradine Drug Mechanismmentioning
confidence: 99%
“…Female representation in the seminal electrophysiological clinical trials was generally low (Figure 2). 115,118,[191][192][193][194][195][196][197][198][199][200] This constitutes a major problem especially in EP because important differences exist between males and females with electrocardiographic and electrophysiological characteristics; incidence and presentation of various arrhythmias; and response to different therapies. These differences make it difficult to generalize overall trial findings to females especially when the number of enrolled females is small.…”
Section: Females and Clinical Trialsmentioning
confidence: 99%